Używki w ciąży - kofeina = Stimulants in pregnancy - caffeine - Agnieszka Konstancja Pawłowska-Muc; Celina Łepecka-Klusek; Grażyna Stadnicka; Anna Bogusława Pilewska-Kozak (Kazimierz Wielki University, 2015)
Pawłowska-Muc Agnieszka Konstancja, Łepecka-Klusek Celina, Stadnicka Grażyna, Pilewska-Kozak Anna Bogusława. Używki w ciąży - kofeina = Stimulants in pregnancy - caffeine. Journal of Education, Health and Sport. 2015;5(6):395-406. ISSN 2391-8306. DOI 10.5281/zenodo.18817 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A395-406 https://pbn.nauka.gov.pl/works/568565 http://dx.doi.org/10.5281/zenodo.18817 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 22.06.2015.   Używki w ciąży - kofeina Stimulants in pregnancy - caffeine   Pawłowska-Muc Agnieszka Konstancja1, Łepecka-Klusek Celina2, Stadnicka Grażyna3, Pilewska-Kozak Anna Bogusława2   [1] Ośrodek Kształcenia Podyplomowego Pielęgniarek i Położnych Radomski Szpital Specjalistyczny im. dr Tytusa Chałubińskiego w Radomiu, ul. Lekarska 4 2 Katedra i Klinika Ginekologii i Endokrynologii Ginekologicznej Uniwersytet Medyczny w Lublinie, Al. Racławickie 23 3 Samodzielna Pracownia Umiejętności Położniczych Uniwersytet Medyczny w Lublinie, ul. Staszica 4/6 1 Postgraduate Training Centre for Nurses and Midwives, Dr Tytus Chałubiński Specialist Hospital in Radom, ul. Lekarska 4 2 Department and Clinic of Gynaecology and Gynaecological Endocrinology, Medical University of Lublin, Al. Racławickie 23 3 Independent Obstetric Skills Workshop, Medical University of Lublin, ul. Staszica 4/6   Adres do korespondencji: mgr piel. Agnieszka Konstancja Pawłowska-Muc Ośrodek Kształcenia Podyplomowego Pielęgniarek i Położnych Radomski Szpital Specjalistyczny im. dr Tytusa Chałubińskiego w Radomiu, ul. Lekarska 4 tel. 48  3615616; fax: 48 3615437 e-mail: agmich@vp.pl   Używki w ciąży - kofeina Streszczenie Wprowadzenie. Kofeina należy do substancji psychoaktywnych, ogólnodostępnych i najbardziej rozpowszechnionych na całym świecie. Jej wpływ na zdrowie kobiet, przebieg ciąży i rozwój płodu jest od lat przedmiotem wielu dyskusji, sporów i dociekań naukowych. Cel pracy. Przegląd piśmiennictwa na temat wpływu działania kofeiny na organizm kobiety oraz skutków jej spożywania w okresie ciąży i laktacji. Skrócony opis stanu wiedzy. Działanie kofeiny na organizm kobiety oraz jej wpływ na przebieg ciąży i zdrowie dziecka nie zostały dotychczas w pełni poznane. Znajduje się ona w wielu produktach, a to sprawia, że jej całkowite, dzienne spożycie jest trudne do oceny.             Podsumowanie. Z przeglądu piśmiennictwa wynika, że duży odsetek kobiet ciężarnych ma zwyczaj codziennego picia herbaty i/lub kawy z kofeiną. Zakres embriotoksycznego działania tej substancji zależy od jej dawki, częstości spożywania oraz stanu zdrowia kobiety ciężarnej. Stanowiska  autorów, co do stosowania napojów zawierających kofeinę w tym czasie, a także ich skutków, są podzielone. Większość jednak podziela pogląd, iż w ciąży i w okresie laktacji należy ograniczyć, a najlepiej zaniechać, spożywanie takich napojów. Zasadne jest zatem, aby działania promujące i wspierające zdrowy styl życia kobiet w wieku rozrodczym dotyczyły, między innymi, tej kwestii. Słowa kluczowe: kofeina, ciężarna, zdrowie, ciąża, płód.   Stimulants in pregnancy - caffeine Summary Introduction. Caffeine belongs to the group of psychoactive substances, which are available to the public and widely propagated around the whole world. Its effect on women's health, the course of pregnancy and the development of the foetus has been the subject of many discussions, arguments and scientific research for many years. Aim. The review of bibliography on the subject of the effects of caffeine on women's organism and the results of its consumption during pregnancy and lactation. Brief description of the state of the art. The effects of caffeine on the organism of a woman and its influence on parturition and the health of the baby have not yet been fully identified. It can be found in many food products, which makes it hard to evaluate its total daily intake. Conclusion. The review of the bibliography indicates that a significant number of pregnant women habitually consumes tea and/or coffee containing caffeine every day. The scope of the embryotoxic effects of this substance depends on its dosage, the frequency of its consumption and the pregnant woman's state of health. The opinions of various authors on the consumption of beverages containing caffeine in this period as well as its effects are divided. However, the majority shares the view that one should limit, or preferably abstain from, drinking such beverages during pregnancy and lactation. It is therefore appropriate for the activities promoting and supporting a healthy lifestyle for women in the reproductive period to pertain to this matter.   Key words: caffeine, pregnant woman, health, pregnancy, foetus.